Persepsi Mahasiswa Prodi Bahasa Dan Kebudayaan Arab Universitas Al Azhar Indonesia Terhadap Urgensi Program Merdeka Belajar Kampus Merdeka - Fazlur Rachman; Zaqiatul Mardiah; Nur Hizbullah (Universitas Al Azhar Indonesia, 2022)
The implementation of the Independent Campus Freedom to Learn program launched by the Ministry of Education and Culture in 2020 caused various reactions from various parties in the higher education sector. Gradually many universities are trying to adapt and encourage students to be able to participate actively in the various types of programs offered. The same reaction was also found among students in the Arabic Language and Culture (BKA) study program at Al Azhar University Indonesia. Various perceptions emerged from students in responding to this MBKM program. This study tries to describe the student's perception, more specifically in terms of three aspects: knowledge of the program, perception of the urgency of the MBKM program, and student interest in participating. The research data was obtained through quantitative research instruments in the form of research questionnaires distributed to all 250 students of the BKA Study Program. After conducting a survey and descriptive statistical analysis it was found that; 1) BKA Study Program students' knowledge of the MBKM program is quite high, 75% of students have received information about the MBKM program with various levels of knowledge, and some are fully aware, know most, and know little, through various sources of information, 2) Student perceptions of the benefits and the urgency of the MBKM program is depicted very positively. Most believe that the program is beneficial for students in developing their competencies and soft skills as a provision to face post-graduate life from university, 3) Student interest and interest is quite high, more than 50% expressed interest in joining the MBKM program, and are even willing to recommend it to colleagues. Among the MBKM programs that are in great demand by students are internships or work practices and student exchanges.Keywords – MBKM Curriculum, Student Perceptions, MBKM Urgency, MBKM Curriculum